Interrogating Gender Roles in Patriarchy in Jamil Ahmad’s The Wandering Falcon - Rai, Kamal (Cognition, 2026)
This paper examines women’s interrogation of traditional gender roles in Ahmad’s novel The Wandering Falcon. Basically, in a male dominated society, women would lack their self autonomy due to the imposition of socio-economic constraints. Women, therefore, are often forced to live a restricted, peripheral life within particular boundaries. However, this paper analyses how women challenge traditional gender roles in pursuit of their liberation. As a counter to the imposed tribal patriarchal societal norms, protagonists Gul Bibi and Shah Zarina resist long-standing tribal laws to pursue their desires and freedom. They make a crucial decision by taking risks with their lives for individual, socio-economic, and sexual autonomy by ignoring their family legacy and societal rules of sexual conduct. Both Gul Bibi and Shah Zarina dare to desert their legitimate husbands and run with the men of their choice by challenging the strict tribal roles. In this way, they intensely resist male-oriented socio cultural and tribal restrictions and obligations, freeing themselves from confined limitations and gaining their freedom. Methodologically, this paper draws on the feminist theorist Simon De-Beauvoir’s The Second Sex and Mary Wollstonecraft’s A Vindication of the Rights of Woman: with Strictures on Political and Moral Subjects to explore women’s challenges to gender-based roles in pursuit of individual freedom. Therefore, this paper uncovers the women’s interrogation of patriarchy and concludes by reflecting on their endeavours to attain individual liberty.